DESIGNING A COMIC STRIP BASED ON KALIMANTAN BARAT FOLKLORE TO SUPPORT TEACHING READING - Noviaty, Gita; ., Ikhsanudin; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research was conducted to design a comic based on West Kalimantan folklore to support teaching reading on narrative text. The research was carried out at SMA Negeri 1 Nanga Pinoh with the tenth grade students in academic year 2015/2016 and their English teacher as the participants. The method of this research was development research which consists of three phases of ADDIE, they are analyze, design and develop. The comis is intended to be supplementary materials in teaching reading on narrative text. From the need analysis, it was found that the students need to improve their reading comprehension with an interesting and eye-catching material. The research focused on creating the material to fit in the needs. To validate the product, an expert validation is used with the result of 86% approval about the validation of the product being made. This result meant that Comic is a very good teaching material for teaching reading on narrative text based on West Kalimantan Folklore. Â Keywords: Comic, Reading Material, Development Research Abstrak: Penelitian ini dilakukan untuk mendesain sebuah komik berdasarkan cerita daerah Kalimantan Barat untuk mendukung pengajaran membaca pada teks naratif. Penelitian ini telah dilaksanakan di SMA Negeri 1 Nanga Pinoh yang melibatkan siswa/i kelas sebelas pada tahun ajaran 2015/2016 dan guru bahasa Inggris mereka sebagai peserta. Metode yang digunakan dalam penelitian ini adalah penelitian pengembangan yang terdiri tiga fase ADDIE yaitu analisis, desain dan pengembangan. Komik digunakan sebagai materi tambahan dalam mengajarkan teks naratif. Pada tahap analisis kebutuhan, diperoleh informasi bahwa siswa/i perlu meningkatkan pemahaman membaca dengan materi yang menarik untuk dipandang. Penelitian ini maka berpusat pada pembuatan materi yang sesuai dengan kebutuhan tersebut. Untuk mengesahkan produk yang didesain, validasi ahli digunakan dengan hasil 86% sebagai validasi yang sah untuk produk yang didesain. Hasil tersebut dapat diartikan bahwa Komik adalah materi pengajaran yang sangat baik untuk digunakan di dalam pengajaran reading pada teks naratif yang berdasarkan cerita daerah Kalimantan Barat. Â Kata Kunci: Komik, Materi Membaca, Penelitian Pengembangan